Class Formation, Labor Market, and Inequality in Gulf Cooperation Council Countries - Erhan Akkaş (İnsan & Toplum)
This paper examines the inequalities between national and non-national workers through class formation in the Gulf Cooperation Council (GCC) countries of Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates. These inequalities are constructed over non-standardized salaries, work conditions, and the rights deprivations that arise from the kafala system due to demographic imbalances in the region. From this point of view, this paper’s main argument is that inequalities exist between nationals and non-nationals in the labor market. At the same time, this paper argues that Gulf states have made some arrangements such as extending the kafala system and controlling salaried payments to eliminate labor market inequalities. The secondary data, including the participation of nationals and non-nationals in the labor market and their minimum and maximum salaries, have been used to present the inequalities in the labor market. This paper uses qualitative analysis and the interpretive technique to provide clear understanding. This paper’s main finding is that although some strategies exist that have increased the rights of non-national workers in the Gulf countries, the salary and personal-rights inequalities in the labor market, as well as discrimination with respect to one’s home country to still exist. In this way, the article’s main objective is to make an essential contribution to the literature on the political economy of Gulf countries by presenting the current situation of nationals and non-nationals in GCC countries’ labor markets following the government regulations that strengthen the labor rights.